Advances in Arbuscular Mycorrhizal Taxonomy - Pagano, M.C. (2016)
Taxonomy, the science of classifying organisms, describes names, identifies organisms, and generates tools for taxonomic identification of fungi. The products of taxonomy are used by taxonomists and ecologists. Correct species names are deliberately used for instance on land management systems to compare ecological interactions between the different components. Current classification systems of Arbuscular mycorrhizal fungi (AMF, Glomeromycota) involve both morphological and molecular tools and their progress shows in some measure a natural organization and understanding of the relationships among species. Several research groups have been discussing the taxonomy, systematics, and evolution of AMF. The researchers may propose their classification system; however, most biologists believe that these developing systems only reflect our knowledge at time. This chapter presents an overview of data showing AMF classification, and recent advances are here compiled. Our goal was to provide nonspecialists such as researchers in other fields and land managers with information on historical and recent changes in AMF classification.